Fresh vs Frozen vs Lyophilized Fecal Microbiota transplant for Recurrent Clostridium Difficile Infection: : A Systematic Review and Network Meta-analysis - Gangwani, Manesh (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.